2004
DOI: 10.1046/j.0105-6263.2003.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cavernous transforming growth factor‐β1 and its Type II Receptor in patients with erectile dysfunction

Abstract: It has been hypothesized that transforming growth factor-beta1 (TGF-beta1) signalling is involved in erectile dysfunction (ED). This study was undertaken to elucidate in detail whether expression of TGF-beta1 and its type II receptor is clinically related to various causes of ED. Fifty-four patients with ED and 24 potent men were the subjects of this study. After multidisciplinary work-up, the ED was classified as psychogenic (n = 6), neurogenic (n = 15), or vasculogenic (n = 33). In every subject, percutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 31 publications
(27 reference statements)
2
50
0
Order By: Relevance
“…Furthermore, it was reported that p42/44 kinase is a downstream effector of the transforming growth factor-beta 1 (TGF-b1) signaling pathway (He et al 2010). TGF-b1 expression is increased in aging trabecular fibroblasts and reported to be the main stimulator of collagen synthesis, inducing cavernosal fibrosis and promoting ED (Ferrini et al 2007;Ryu et al 2004). We hypothesize that increased p42/44 activation in aged ECM component may be a downstream event of the TGF-b1 pathway, adding a new piece in the complex puzzle of aging CC signaling events.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, it was reported that p42/44 kinase is a downstream effector of the transforming growth factor-beta 1 (TGF-b1) signaling pathway (He et al 2010). TGF-b1 expression is increased in aging trabecular fibroblasts and reported to be the main stimulator of collagen synthesis, inducing cavernosal fibrosis and promoting ED (Ferrini et al 2007;Ryu et al 2004). We hypothesize that increased p42/44 activation in aged ECM component may be a downstream event of the TGF-b1 pathway, adding a new piece in the complex puzzle of aging CC signaling events.…”
Section: Discussionmentioning
confidence: 88%
“…[32][33][34] Clinical studies have shown that cavernosal TGFbeta1 expression is significantly greater in vasculogenic ED patients than in the control subjects or psychogenic ED patients. 35 TGF-beta1 type II receptor expression was also found to be significantly greater in vasculogenic ED compared with control subjects and patients with psychogenic and neurogenic ED. 35 Patients with vascular risk factors such as hyperlipidemia and atherosclerosis were found to have significantly greater degrees of cavernosal fibrosis than those without these conditions.…”
Section: Changes In Tgf-beta Expressionmentioning
confidence: 82%
“…35 TGF-beta1 type II receptor expression was also found to be significantly greater in vasculogenic ED compared with control subjects and patients with psychogenic and neurogenic ED. 35 Patients with vascular risk factors such as hyperlipidemia and atherosclerosis were found to have significantly greater degrees of cavernosal fibrosis than those without these conditions. 35 Furthermore, this study has shown that the abundance of collagen fibers closely correlates with both TGF-beta1 and TGF-beta1 receptor II expression, suggesting a role of TGF-beta1 and its receptor II in cavernosal fibrosis in vasculogenic ED patients.…”
Section: Changes In Tgf-beta Expressionmentioning
confidence: 82%
See 2 more Smart Citations